Discourse analysis in the contemporary Islamic garden framework - Abdul Latiff, Zainab; Mohd Yaman, Maheran (American Scientific Publishers, 2017)
Discourse analysis was primarily understood to analyze qualitative data in the nature of communication and words. It was also used to be more common in the field of language related studies more than in the field of urban planning. In the present day, it is evident that more journals on urban planning that employs method related to discourse analysis are being published. However, less research has been carried out in an interdisciplinary approach that allows for an integration of knowledge in policy-based urban planning and design-based landscape architecture. This article deals with the ways of how discourse analysis is utilized in an interdisciplinary study i.e., urban planning and landscape architecture to forge a new conceptual framework of Malaysia contemporary Islamic garden. However, there are some drawbacks linked to this approach in which alternatives are essential to be prepared beforehand.